The front porch club - Major, Michelle (Major, Michelle. Carolina girls, 2023)
Annalise Haverford, Shauna Myer, and Meghan Banks have little in common, and even some bad blood, but when life's complications threaten to drown them, they'll have to rely on each other to stay afloat.